Cardioprotective effects of a novel iron chelator, pyridoxal 2-chlorobenzoyl hydrazone, in the rabbit model of daunorubicin-induced cardiotoxicity - Sterba, Martin; Popelová, Olga; Simunek, Tomás; Mazurová, Yvona; Potácová, Anna; Adamcová, Michaela; Kaiserová, Helena; Ponka, Premysl; Gersl, Vladimír (The Journal of pharmacology and experimental therapeutics, 2006)
Iron chelation is the only pharmacological intervention against anthracycline cardiotoxicity whose effectiveness has been well documented both experimentally and clinically. In this study, we aimed to assess whether pyridoxal 2-chlorobenzoyl hydrazone (o-108, a strong iron chelator) can provide effective protection against daunorubicin (DAU)-induced chronic cardiotoxicity in rabbits. First, using the HL-60 leukemic cell line, it was shown that o-108 has no potential to blunt the antiproliferative efficacy of DAU. Instead, o-108 itself moderately inhibited cell proliferation. In vivo, chronic DAU treatment (3 mg/kg weekly for 10 weeks) induced mortality (33%), left ventricular (LV) dysfunction, a troponin T rise, and typical morphological LV damage. In contrast, all animals treated with 10 mg/kg o-108 before DAU survived without a significant drop in the LV ejection fraction (63.2 +/- 0.5 versus 59.2 +/- 1.0%, beginning versus end, not significant), and their cardiac contractility (dP/dt(max)) was significantly higher than in the DAU-only group (1131 +/- 125 versus 783 +/- 53 kPa/s, p < 0.05), which corresponded with histologically assessed lower extent and intensity of myocardial damage. Although higher o-108 dose (25 mg/kg) was well tolerated when administered alone, in combination with DAU it led to rather paradoxical and mostly negative results regarding both cardioprotection and overall mortality. In conclusion, we show that shielding of free intracellular iron using a potent lipophilic iron chelator is able to offer a meaningful protection against chronic anthracycline cardiotoxicity. However, this approach lost its potential with the higher chelator dose, which suggests that iron might play more complex role in the pathogenesis of this disease than previously assumed.
Keywords: Stroke Volume; Electrocardiography; Ventricular Function, Left; Male; funkce levé komory srdeční; činčila; Chinchilla; protinádorová antibiotika; Hydrazones; HL-60 buňky; hydrazony; Troponin T; Heart Rate; Heart Diseases; Myocardium; Iron Chelating Agents; chelátory železa; daunomycin; mužské pohlaví; srdeční frekvence; tepový objem; buněčné dělení; troponin T; králíci; pyridoxal; Body Weight; Pyridoxal; minutový srdeční výdej; Myocardial Contraction; Cardiotonic Agents; Animals; lidé; Cell Division; krevní tlak; Daunorubicin; HL-60 Cells; Humans; zvířata; Antibiotics, Antineoplastic; Blood Pressure; kardiotonika; nemoci srdce; Rabbits; kontrakce myokardu; tělesná hmotnost; Cardiac Output; myokard; elektrokardiografie